Diffusion-tensor imaging for differentiating uterine sarcoma from degenerative uterine fibroids. Issue 4 (April 2021) - Tian, S.; Niu, M.; Xie, L.; Song, Q.; Liu, A.
Abstract : AIM: To explore the applicability of diffusion-tensor imaging (DTI) sequence quantitative parameters in differentiating uterine sarcoma (USr) from degenerative uterine fibroids (DUF). MATERIALS AND METHODS: Fourteen cases of USr and 30 cases of DUF were analysed retrospectively. The diffusion-weighted imaging (DWI) and DTI images were analysed by two observers using Functool software on a ADW4.6 workstation. The images were post-processed to generate an apparent diffusion coefficient (ADC) map of DWI, ADC map of DTI (ADC T map), and fractional anisotropy (FA) map. Three regions of interest (ROI) were selected from the ADC, ADC T, and FA maps to obtain the ADC, ADC T, and FA values. The receiver operating characteristic (ROC) curves of all parameters were used to analyse and compare the diagnostic value of USr and DUF. RESULTS: The ADC value, ADC T value, and FA value of USr (1.190 ± 0.262 × 10 −3 mm 2 /s, 1.165 ± 0.270 × 10 −9 mm 2 /s, 0.168 ± 0.063) were significantly lower compared to the values for DUF (1.525 ± 0.314 × 10 −3 mm 2 /s, 1.650 ± 0.332 × 10 −9 mm 2 /s, 0.254 ± 0.111; all p <0.001). The diagnostic threshold values for USr were: ADC ≤1.290 × 10 −3 mm 2 /s, ADC T ≤1.322 × 10 −9 mm 2 /s and FA ≤0.192. The corresponding sensitivities and specificities were 78.6%/90%, 96.7%/92.9%, and 86.7%/85.7%, respectively. The areas under the curve (AUC) were 0.875, 0.974, and 0.831, respectively. CONCLUSIONS: DTI quantitative parameters can be used to differentiate USr from DUF. The ADC T value had the highest diagnostic efficacy. Highlights: DTI can identify uterine sarcoma (USr) and degenerative uterine fibroids (DUF). The ADC T and FA values of USr were significantly lower compared to DUF values. Amongst DTI parameters the ADC T has the high diagnostic efficacy for USr and DUF.